Sectarian Fanaticism in Baghdad and its Most Prominent Manifestations in The 5th Century AH - Seggani, Souheila; Abdul Hamid, Ahmad Faisal Faisal; Mohd nor, Mohd Roslan (Journal Al-Muqaddimah, 2017)
In the fifth Hijri century, sectarian fanaticism has emerged in its strongest and most acute forms. Baghdad, the capital of the caliphate, has suffered a lot from its seditions and events. Under the state of Bojana, the Shi’ite intellectual movement was activated in Baghdad and it has developed leading to violent reactions of Sunnis who have been threatened in their intellectual and national security. This article discusses the political and doctrinal circumstances and their role in the emergence of this fanaticism and it highlights their manifestations of the sedition (fitnah) that have arisen and led to fighting between Shiites and Sunnis, which continued to carry out the Seljuk state, but at a lesser pace due to the persecution of the Seljuk authorities of the Shi’a in an attempt to revive the sunnah’s curriculum in the community. Additionally, the researcher sheds light on other ideological conflicts that emerged after the middle of the fifth Hijri century between Sunni parties such as Hanninas and Ashasrah. The researcher relies on the descriptive historical approach, and concludes that those ideological differences, characterized by the character of the hyperbole, fanaticism and indulgence of atonement led to the absence of tolerance for the other and the controversy that is better, as well as these differences led to the neglect of the moderate approach through behavior. In addition, leaders and some scholars have dramatically fuelled the fires sedition (fitnah) and they crowd people to participate in which seriously affected the intellectual security of the Islamic Ummah. This security which is the basis for all other types of security and that is achieved by the Islamic nation’s reservation of its religion, culture and affiliation